2020
DOI: 10.1002/pbc.28278
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the preliminary efficacy of Pain Buddy: A novel intervention for the management of children's cancer‐related pain

Abstract: Objectives Cancer‐related pain in children is prevalent and undermanaged. Mobile health (mHealth) applications provide a promising avenue to address the gap in pain management in children with cancer. Pain Buddy is a multicomponent mHealth application developed to manage cancer‐related pain in children. The goal of this paper is to present preliminary efficacy data of the impact of Pain Buddy on children's pain severity and frequency. Methods In a randomized controlled trial over 60 days, children (N = 48) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The key features that our research detected were the following: symptom tracker, pain-related symptom tracker, communication with medical staff, adherence to treatment, information provision, social support, and coping strategies. More specifically, in this review communication with medical staff seemed to be highly important as it was the most frequently applied feature with 18 articles confirming it (4,9,10,(12)(13)(14)17,18,20,21,(25)(26)(27)(28)(29)36,39,40). Subsequently, also 17 studies included the feature of adherence to treatment (7,10-12,14-17,19,24-26,29,36,37,39,40).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The key features that our research detected were the following: symptom tracker, pain-related symptom tracker, communication with medical staff, adherence to treatment, information provision, social support, and coping strategies. More specifically, in this review communication with medical staff seemed to be highly important as it was the most frequently applied feature with 18 articles confirming it (4,9,10,(12)(13)(14)17,18,20,21,(25)(26)(27)(28)(29)36,39,40). Subsequently, also 17 studies included the feature of adherence to treatment (7,10-12,14-17,19,24-26,29,36,37,39,40).…”
Section: Resultsmentioning
confidence: 88%
“…Also, throughout literature there are more 14 studies encompassed the feature of information provision (4,7,9,10,12,18,21,(24)(25)(26)(27)29,36,40). Furthermore, painrelated symptom tracker was the following used feature with 13 studies confirming it (2,7,10,(12)(13)(14)(15)(17)(18)(19)(20)25,28). Also, the facility of social support was found in 13 researches (4,7,9,10,21,23-25,27,32-34,36,40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used in very few studies, but it is recommended for routine use in clinical practice and research [26]. In a study in which the effectiveness of Pain Buddy was evaluated through APTT, less moderate to severe pain was experienced in the intervention group [27]. However, no study with a large pediatric population with cancer using APTT was found.…”
Section: Discussionmentioning
confidence: 99%